Analyzing Employee Engagement Survey to Identify the Engagement Drivers of Talent Employee at PT Bank BNI Syariah - Putri Imuri, Evinka; Ros Bangun, Yuni (The Indonesian Journal of Business Administration, 2019)
Abstract. In most industries, retaining high performance employee is challenging issue faced by all companies, included in banking industry, which not only in conventional banking but also in sharia banking including PT Bank BNI Syariah as the third largest asset in sharia banking industry.  From the total turnover and total talent employee resigned compared to other competitor BNI Syariah should identify the suitable strategy to retain those employee. By designing and conducting the employee engagement survey, author try to identify which driver of employee engagement drivers that is most significant influence to say, stay and strive behavior towards company. 69% of talent employee participated in this research and give The study confirms that The Basic driver become the most influential engagement driver for say, stay and strive engagement outcomes and leadership become the least influencing among others. From the matrix influencing and variable score the basic also become the most critical drivers that must be improved because the result which reflect the current condition was not really satisfied moreover the basic itself was the most significant factor to the employee engagement of talent employee BNI Syariah  From the result, therefore, the proposed program as a retain strategy are related with the remuneration, culture, and performance management system strategy.Keywords: Bank, Employee Engagement, Human Resource, Talent Employee, Talent Management, Sharia Bank.